Analyzing perception of Over-The-Top (OTT) sports broadcasting focus on social media big data analytics - Wonyong Jang; Jaeyeon Hwang (Heliyon)
The purpose of this study was to analyze Korean subscribers' perceptions of sports broadcasting on OTT platforms. To achieve this, data was collected from various sources between 2018 and 2022 using ‘OTT sports broadcasting’ as the keyword, employing a big data processing solution called ‘Textom.’ The results were as follows: First, text mining was conducted to analyze word frequencies and examine TF-IDF scores. The text mining analysis revealed that words such as “broadcasting,” “sports,” “service,” and “game” were used most frequently. In contrast, the TF-IDF analysis showed high scores for words like “SPOTV,” “broadcasting,” “Tottenham,” and “live broadcast.” Second, degree centrality and CONCOR analyses were employed for semantic analysis. The results indicated that degree centrality produced findings similar to the rankings based on word frequency. However, differences were observed in the rankings between degree centrality and TF-IDF. Next, a CONCOR analysis was conducted to explore the cluster relationships among words associated with the perception of ‘OTT sports broadcasting.’ This analysis resulted in the formation of four clusters consisting of words with similar characteristics: ‘OTT soccer broadcasting,’ ‘Sports OTT platform,’ ‘OTT platform operator,’ and ‘Overseas sports broadcasting.’